Chapter Unmanned Maritime Systems for Search and Rescue - Matos, Aníbal (InTechOpen, 2017)
The development of maritime unmanned tools for search and rescue operations is not a trivial task. A great part of maritime unmanned systems developed did not target such application, being more focused on environmental monitoring, surveillance or defence. In opposition to these applications, search and rescue operations need to take into account relevant issues such as the presence of people or other vessels on the water. Building upon user requirements and overall integrated components for assisted rescue and unmanned search operations (ICARUS) system architecture, this chapter addresses the development of unmanned maritime systems. It starts with an overview of the approach where a two‐tier solution was adopted to address safety issues and then proceeds to detail each of the developed technologies.